2019
DOI: 10.22219/jrak.v9i1.7175
|View full text |Cite
|
Sign up to set email alerts
|

Technology Acceptance Model as a Predictor of Simda Usage

Abstract: The study aims to analyze behavioral aspects, especially individual factors that influence the use of SIMDA using the Technology Acceptance Model theory (TAM). This research uses a positivistic approach or commonly called quantitative research. The population in this study were all financial managers in all Organisasi Perangkat Daerah (OPD) in the Pemerintah Kabupaten Pasuruan with a total sample of 282 respondents. The samples selected by judgment sampling method. The analysis was conducted using Partial Leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…This means that the greater the usefulness and ease of using an application, the greater the user's interest to use it. The results of this study support the research of Febrianti et al (2019) who tested this effect on the use of SIMDA. The same research results found by Chuang et al (2016) and also Iqbal and Ahmed Bhatti (2015), namely the perception of usefulness and convenience has a positive effect on attitudes to use new technology.…”
Section: Hypothesis Testingsupporting
confidence: 87%
See 1 more Smart Citation
“…This means that the greater the usefulness and ease of using an application, the greater the user's interest to use it. The results of this study support the research of Febrianti et al (2019) who tested this effect on the use of SIMDA. The same research results found by Chuang et al (2016) and also Iqbal and Ahmed Bhatti (2015), namely the perception of usefulness and convenience has a positive effect on attitudes to use new technology.…”
Section: Hypothesis Testingsupporting
confidence: 87%
“…The constructs used are perceived usefulness, perceived ease of use, attitude, behavioral intention, and actual technology usage. (Febrianti, Hariadi, & Baridwan, 2019;Mustakini, 2007).…”
Section: Figure 1 Funding Informationmentioning
confidence: 99%
“…The Structural Equation Modeling (SEM) calculation results show a significance level of 0.000 < 0.05. The effect shown by the beta coefficient is positive (H3 is supported), meaning that the higher output quality will increase the perceived usefulness of the VAMS application (Febrianti et al, 2019, Maksum et al, 2017.…”
Section: The Effect Of the Output Quality On The Perceived Usefulnessmentioning
confidence: 88%
“…In this condition, the user is faced with the complexity of working on a job-concurrent in multiple positions. Implementing new systems, individual behavior becomes an essential factor to consider because the level of readiness of users to accept the new system and employee attitudes towards the new system has a major influence on the success or failure of the system implementation (Febrianti et al, 2019). In the Technology Acceptance Model (TAM), predicting the acceptance of the use of technology is mainly determined by the perceived ease of use (PEU) and perceived usefulness (PU) of the system and technology being implemented (Davis, 1989, Venkatesh and Bala, 2008, Winarno et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation